A Patient Diagnosed with Mosaic Trisomy 18 Presenting New Symptoms: Diaphragmatic Relaxation and Cyclic Vomiting Syndrome. Updated Review of Mosaic Trisomy 18 Cases - Kósa, Magdolna; Horváth, Emese; Kalmár, Tibor; Maróti, Zoltán; Földesi, Imre; Bereczki, Csaba (Journal of Pediatric Genetics, 2022)
Although data on T18 are widespread, there is a lack of knowledge on mosaic trisomy 18 (mT18). A current review of mT18 symptomatology, long-term follow-up, and potential health risks is lacking for health care professionals. Our paper addresses these, emphasizing the importance of regular tumor screening as a key message for mT18 patient follow-up. We also present the case of a female patient with mT18 who presented with diaphragmatic relaxation and cyclic vomiting syndrome (CVS), which had previously not been reported in this genetic condition. On further investigating the etiology of CVS, we revealed a novel mitochondrial mutation in the MT-ND6 gene in heteroplasmic form. Based on the literature, we hypothesize that the mitochondrial mutation together with mT18 could result in CVS.
Keywords: mosaic trisomy 18; follow-up; cyclic vomiting syndrome; MT-ND6 mutation; diaphragmatic relaxation